Improved chlorine tolerance of a polyvinyl pyrrolidone-polysulfone membrane enabled by carboxylated carbon nanotubes. (1st November 2016) - Xie, Pengchao; de Lannoy, Charles-François; Ma, Jun; Wang, Zongping; Wang, Songlin; Li, Jingjing; Wiesner, Mark R.
Abstract: Chemical cleaning of membranes may be limited by the tolerance of some polymeric membranes to chlorine. In this work we show that modification of a polyvinyl pyrrolidone-polysulfone (PVP-PSF) membrane with carboxylated carbon nanotubes (CNTs) leads to greater chlorine tolerance of the membrane along with smoothing the surface roughness and improving some membrane properties including permeability, hydrophilicity and antifouling ability. In comparison with PVP-PSF membrane, incorporating carboxylated CNTs reduced the release of organic matter from the membrane and caused less decrease in hydrophilicity, permeability and BSA rejection. After chlorine treatment of a conventional PVP-PSF membrane, an infrared absorbance peak around 1670 cm −1, representing the vibration of the amide bond in the PVP, decreased significantly and two smaller peaks at around 1725 and 1775 cm −1 were observed. The percentage of C−Cl (2p) in the PVP-PSF membrane was about 2.8 times greater than that of the carboxylated CNT-composite PVP-PSF (CNT-PVP-PSF) membrane after chlorine exposure, suggesting greater chlorine tolerance of CNT-PVP-PSF membrane. In comparison with PVP-PSF membrane, the formation of toxic chlorinated byproducts during chlorination of organic matter released from CNT-PVP-PSF membrane was much lower. The improvement of tolerance to chlorine is attributed to stabilization of the polymer through hydrogen bonding between polymer and carboxylated CNTs. Graphical abstract: Highlights: Carboxylated CNTs were suggested to improve chlorine tolerance of PVP-PSF membrane. Hydrogen bonds in CNT-PVP-PSF membrane might contribute to the increase of chlorine tolerance. Carboxylated CNTs may decrease the formation of chlorinated byproducts during chlorination.